Principles of neural network artificial immune system design to detect attacks on computers - Golovko, Vladimir; Komar, Myroslav; Sachenko, Anatoly (Видавництво Львівської політехніки, 2010)
It’s proposed to use artificial immune systems and neural networks to detect attacks on computer systems. The principles of attack detection system design based on artificial immune network are described, and the architecture of attack detection system is presented.
Keywords: intrusion detection systems; computer network security; neural networks; artificial immune systems; immune detectors